KERJA KERAS DALAM ISLAM - Mabrur, Haqi (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2021)
Islam as a religion and ideology encourages its people to work hard, but not forgetting to worship. Islam as a religion that is syamil and kamil also provides guidelines on hard work that makes work not only a search for sustenance but more from a transcendental dimension and at the same time a human identity itself. Hard work is interpreted as a human attitude or view of the work done, which is dilated by the values he believes in. work is all dynamic activities and has the goal of fulfilling certain needs (physical and spiritual), and in achieving that goal he tries with all sincerity to achieve optimal performance as proof of his dedication to Allah SWT. As a Muslim, he should obey his religion which has provided limits according to the principles of Islamic work, namely work must be upheld on the basis of piety, work determines human value, work is determined by quality not quantity, work must be done with knowledge, and work produces knowledge. .Key Word: concept, hard work, Islam